2009
DOI: 10.1016/s0377-1237(09)80051-8
|View full text |Cite
|
Sign up to set email alerts
|

Cation Exchange High Performance Liquid Chromatography for Diagnosis of Haemoglobinopathies

Abstract: The simplicity of the sample preparation, superior resolution of the method and accurate quantitation of haemoglobin concentration, combined with complete automation, makes this an ideal methodology for diagnosis of haemoglobinopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…These conventional methods are family history, clinical features, hemoglobin level, red blood cell indices, red cell count, peripheral blood smear study, Hb A2 quantification, Hb F quantification, cellulose acetate electrophoresis at alkaline pH for hemoglobin and sickling test. Various drawbacks and shortcomings of these methods are that Hb S,G,D,Q and Lepore have same mobility on electrophoresis and Hb A2,C and E also have same mobility [6] . Double heterozygous states also are difficult to diagnose [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conventional methods are family history, clinical features, hemoglobin level, red blood cell indices, red cell count, peripheral blood smear study, Hb A2 quantification, Hb F quantification, cellulose acetate electrophoresis at alkaline pH for hemoglobin and sickling test. Various drawbacks and shortcomings of these methods are that Hb S,G,D,Q and Lepore have same mobility on electrophoresis and Hb A2,C and E also have same mobility [6] . Double heterozygous states also are difficult to diagnose [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Various drawbacks and shortcomings of these methods are that Hb S,G,D,Q and Lepore have same mobility on electrophoresis and Hb A2,C and E also have same mobility [6] . Double heterozygous states also are difficult to diagnose [6] . Clinical and laboratory features have low specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Gupta et al mean Hb was found to be 9.3 gm%. 9 Lower hemoglobin in some of our cases could be due to associated iron deficiency ( Table 3). The hemoglobinopathies, particularly β-thalassemias are a considerable health problem.…”
Section: Discussionmentioning
confidence: 81%
“…Mean Hb of antenatal group was found to be 9.1 gm % which was slightly lower than the student group 10.9 gm %. In a study done by Gupta et al [17] mean Hb was found to be 9.3 gm%. Lower hemoglobin in some of our cases could be due to associated iron deficiency.…”
Section: Discussionmentioning
confidence: 87%